Clinical Management of Patients with Schizophrenia Treated with Long-Acting Injectable Antipsychotics and Telepsychiatry Use During COVID-19 Pandemic. (April 2022) - Bessonova, Leona; Keane, Elizabeth; Achtyes, Eric; Harvey, Philip D.; Kane, John M.; Saklad, Stephen R.; Trotter, Jeffrey; Claxton, Amy; Hatfield, Tiffany; McGrory, James; Noori, Wahidullah; O'Sullivan, Amy K.; et al.
Abstract: Background: The COVID-19 pandemic substantially impacted care of patients with schizophrenia treated with long-acting injectable antipsychotics (LAIs). This study examined how clinics adapted operations to maintain a standard of care for these patients after pandemic onset. Methods: Online surveys were completed in October-November 2020 by one principal investigator (PI) or PI-appointed designee at 35 clinics participating in OASIS (NCT03919994). Items concerned pandemic impacts on clinic operations, particularly telepsychiatry, and on the care of patients with schizophrenia treated with LAIs. Results: All 35 clinics reported using telepsychiatry; 20 (57%) implemented telepsychiatry after pandemic onset. Telepsychiatry visits increased from 12%-15% to 45%-69% across outpatient visit types after pandemic onset; frequency of no-show and/or canceled telepsychiatry visits decreased by approximately one-third. Nearly half of clinics increased the frequency of telepsychiatry visits for patients with schizophrenia treated with LAIs. Approximately one-third of participants each reported switching patients treated with LAIs to longer injection interval LAIs or to oral antipsychotics. The most common system/clinic- and patient-related barrier for telepsychiatry visits was lower reimbursement rate and access to technology/reliable internet, respectively. Almost all participants (94%) were satisfied with telepsychiatry for maintaining care of patients with schizophrenia treated with LAIs; most predicted a hybrid of telepsychiatry and office visits post-pandemic. Conclusions: Changes made by clinics after pandemic onset were viewed by almost all participants as satisfactory for maintaining a standard of care for patients with schizophrenia treated with LAIs. Most participants predicted continuing telepsychiatry to support patient care post-pandemic; equitable access to telepsychiatry will be important in this regard. Funding: Alkermes, Inc.